PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN ULASAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKINCARE AZARINE DI KOTA BATAM - Ludina Giawa; Nora Pitri Nainggolan (SCIENTIA JOURNAL, 2026)
This research to examine the influence of brand image, product quality, and product reviews on purchasing decisions for Azarine Skincare in Batam City. The study was conducted using a quantitative approach using a sample of 100 respondents, namely all Azarine consumers in Sagulung District, Batam City. The data used were primary data obtained directly from respondents, then analyzed using the SPSS version 26 application. The results showed that brand image had a positive and significant influence on purchasing decisions for Azarine Skincare in Batam City. In addition, product quality was also proven to have a positive and significant influence on purchasing decisions. Product reviews showed a positive and significant influence on purchasing decisions for Azarine Skincare in Batam City. Simultaneously, brand image, product quality, and product reviews had a positive and significant influence on purchasing decisions for Azarine Skincare in Batam City